Encephalopathy in COVID-19 Presenting With Acute Aphasia Mimicking Stroke - Pensato, Umberto; Muccioli, Lorenzo; Pasini, Elena; Tappatà, Maria; Ferri, Lorenzo; Volpi, Lilia; Licchetta, Laura; Battaglia, Stella; Rossini, Giada; Bon, Isabella; Re, Maria Carla; Cirillo, Luigi; et al. (Frontiers in Neurology, 2020)
Introduction: Neurological manifestations are emerging as relatively frequent complications of COVID-19, including stroke and encephalopathy. Coagulopathy and endothelial dysfunction secondary to infection have being suggested as putative cause of stroke. Case: A middle-aged man presented with acute language disturbance at the emergency department. Examination revealed expressive aphasia, mild ideomotor slowing and severe hypercapnic hypoxemia. Multimodal CT assessment and EEG did not reveal any abnormalities. COVID-19 was diagnosed based on chest CT findings and positive SARS-CoV-2 RT-PCR on nasopharingeal swab. The following day, neurological symptoms progressed to agitated delirium and respiratory status worsened, requiring admission to the ICU and mechanical ventilation. Brain MRI and CSF studies were unremarkable. RT-PCR for SARS-CoV-2 on CSF was negative. He received supportive treatment and intravenous low-dose steroids. His neurological and respiratory status resolved completely within two weeks. Conclusions: We report a patient with reversible COVID-19-related encephalopathy presenting as acute aphasia, mimicking stroke or status epilepticus, eventually evolving into delirium. Although large-vessel stroke is frequently encountered in COVID-19, our case suggests that focal neurological deficits may occur as the earliest feature of encephalopathy. Neurological status reversibility and the absence of abnormalities on brain MRI are consistent with a functional rather than a structural neuronal network impairment.